Consumo de alcohol y sustancias psicoactivas en estudiantes de la Seccional Oriente de la Universidad de Antioquia (2015)
ABSTRACT: The objective of this research is to describe the frequency, intensity, level of risk and correlations of the types of alcohol and psychoactive substances in young students of the Eastern branch of the University of Antioquia. It is an empirical analytical cross-sectional design, using a representative sample of 306 randomized participants. To detect the types of consumption AUDIT and DAST 10 instruments were used. The results show that alcohol is the most widely consumed psychoactive substance, that a considerable number of students use drugs and reported difficulties, and there are multiple relationships between alcohol and other drug use in terms of frequency, intensity, implications and consequences.